2014
DOI: 10.1007/s12350-013-9814-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel attenuation correction of SPECT images using scatter photopeak window data for the detection of coronary artery disease

Abstract: Attenuation correction with SSPAC may be a feasible method of correction for myocardial perfusion SPECT and in some cases may provide better accuracy for diagnosing coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Yamauchi et al (4) reported that the automatic processing success rate of SSPAC was 93%. They used low counts, and SSPAC was not successful in the stress condition, but aμmap made in a resting-condition study with a high count can be used under stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamauchi et al (4) reported that the automatic processing success rate of SSPAC was 93%. They used low counts, and SSPAC was not successful in the stress condition, but aμmap made in a resting-condition study with a high count can be used under stress.…”
Section: Discussionmentioning
confidence: 99%
“…The SSPAC method, which recognizes the outlines of the body around chest and lungs using scatter window data, is known to reduce misregistration problems by its method of constructing aμmap (4). However, when injecting a low dose, the quality of the Compton scatter image and the recognition accuracy of the outlining decrease (5), such that a μ map image cannot be constructed.…”
mentioning
confidence: 99%
“…The same group of investigators reported slightly different results in a previous study, with improved sensitivity for LAD disease and improved specificity for RCA disease with the use of SSPAC. 12 There are several potential advantages of the SSPAC method.…”
Section: Termination Of Exercise At Onset Of Ischemia In the Region Wmentioning
confidence: 99%
“…We chose the method called the scatter and photo peak window data for our Attenuation Correction (SSPAC) technique [6] rather than employ a correction based on an X-ray CT. This choice was made to avoid increasing the radiation exposure to the pediatric patient.…”
Section: Attenuation Correctionmentioning
confidence: 99%